Ionize Hard: Interstellar PO+ Detection - Rivilla, Víctor M.; García De La Concepción, Juan; Jiménez-Serra, Izaskun; Martín-Pintado, Jesús; Colzi, Laura; Tercero, Belén; Megías, Andrés; López-Gallifa, Álvaro; Martínez-Henares, Antonio; Massalkhi, Sara; Martín, Sergio; Zeng, Shaoshan; et al. (Frontiers in Astronomy and Space Sciences, 2022)
We report the first detection of the phosphorus monoxide ion (PO+) in the interstellar medium. Our unbiased and very sensitive spectral survey towards the G+0.693$-$0.027 molecular cloud covers four different rotational transitions of this molecule, two of which (J=1-0 and J=2-1) appear free of contamination from other species. The fit performed, assuming Local Thermodynamic Equilibrium conditions, yields a column density of N=(6.0+-0.7)x10^{11} cm^{-2}. The resulting molecular abundance with respect to molecular hydrogen is 4.5x10^{-12}. The column density of PO+ normalised by the cosmic abundance of P is also larger than those of NO+ and SO+, normalized by N and S, by factors of 3.6 and 2.3, respectively. The N(PO+)/N(PO) ratio is 0.12+-0.03, more than one order of magnitude higher than those of N(SO+)/N(SO) and N(NO+)/N(NO). These results indicate that P is more efficiently ionised in the ISM than N and S. We have performed new chemical models that confirm that the PO+ abundance is strongly enhanced in shocked regions with high values of cosmic-ray ionisation rates (10^{-15}-10^{-14} s^{-1}), as occurs in the G+0.693-0.027 molecular cloud. The shocks sputter the interstellar icy grain mantles, releasing into the gas phase most of their P content, mainly in the form of PH3, which is converted into atomic P, and then ionised efficiently by cosmic rays, forming P+. Further reactions with O2 and OH produces PO+. The ionisation of PO might also contribute significantly, which would explain the high N(PO+)/N(PO) observed. The relatively high gas-phase abundance of PO+ with respect to other P-bearing species stresses the relevance of this species in the interstellar chemistry of P.